Promotion and Marketing Communications 2020
DOI: 10.5772/intechopen.89988
|View full text |Cite
|
Sign up to set email alerts
|

International Market Segmentation across Consumption and Communication Categories: Identity, Demographics, and Consumer Decisions and Online Habits

Abstract: In this chapter we will discuss the different approaches to market segmentation and selection and explore how the selection process influences the company's culture, its brand positioning, and how it is impacted upon by the overall marketing and communication strategy and vice versa. Some questions this chapter considers and discusses are: Which segments should firms' international marketing activities (including financial, human resources, and the firm's capabilities) focus on? How do multinationals decide if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Oeconomia 20 �2�, 13-20, doi: 10.22630�ASPE.2021.20.2.11 doi: 10.22630�ASPE.2021 This cluster analysis confirms the importance of demographic variables and behavioural characteristics as important tools in the touristic market segmentation for visitors to Gjirokastra. These variables are considered to be important as noted by previous researchers examining market segmentation [Dolnicar 2002, Perdue 2004, Kazeminia et al 2013, Camilleri 2017, De Villiers et al 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oeconomia 20 �2�, 13-20, doi: 10.22630�ASPE.2021.20.2.11 doi: 10.22630�ASPE.2021 This cluster analysis confirms the importance of demographic variables and behavioural characteristics as important tools in the touristic market segmentation for visitors to Gjirokastra. These variables are considered to be important as noted by previous researchers examining market segmentation [Dolnicar 2002, Perdue 2004, Kazeminia et al 2013, Camilleri 2017, De Villiers et al 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Marketers further differentiate between buyers and divide them into smaller segments that are fairly homogeneous in terms of need, resources, location, buying attitudes, or buying practices. The main purpose of segmentation activities is to ensure that potential and current customers can be reached more effectively and that communication, product, and service offerings can be matched to the unique needs of different consumers [De Villiers et al 2019].…”
Section: Main Debatesmentioning
confidence: 99%
“…Integrated marketing communications may also become more valuable with localized automated applications (IMC). When past are examined, it is concluded that the probability of IMC being successful is higher when it contains cultural, communication activities, language, and socio-demographic differences (De Villiers et al, 2020).…”
Section: The Role Of Automated Analysis At the Enterprise Level: Gloc...mentioning
confidence: 99%
“…The model has divided customers into groups groupings characterized by three index values: relevance (once customers can directly make most latest acquisition), recurrence (how often the consumer makes transactions), and financial value (how much the purchaser gets to spend on each purchase), and then gives e-commerce businesses the operational measures they need to keep potential customers and enhance profitability. Way of categorizing, but on the other side, has a significant wait than some other types of client information, especially data on browsing habits [5], [6]. Furthermore, various clients' repurchase cycles are different.…”
Section: Introductionmentioning
confidence: 99%